Hip fractures: public perceptions are we jumping the gun? - Weston, N (Royal College of Surgeons, 2012)
McBride TJ, Panrucker S, Clothier JC Hip fractures: public perceptions. Ann R Coll Surg Engl 2011; 93: 67–70 doi: 10.1308/003588411X12851639107034